Penindakan terhadap Kendaraan Motor Dalam Penggunaan Knalpot Racing di Ruang Lingkup Kampus Demi Kenyamanan Kegiatan Belajar Mengajar - Irwansyah Irwansyah; Farouhu Waroyhan (EduInovasi: Journal of Basic Educational Studies, 2023)
A campus is one place where teaching and learning processes take place. One factor in creating a comfortable and quiet learning environment is avoiding noise problems. A comfortable campus environment not only affects the conditions of the campus environment, but also the facilities and services of the campus, which can affect the learning success of students. One common noise problem in campus environments is the use of electric vehicles with racing exhaust by students. In addition to students, many instructors have complained about the problem that using this extraction system on campus makes it difficult for users of this extraction system to hear when passing buildings or courses that are close to roads or parking lots. It is clear from the results of the research conducted that there is no campus policy to address this issue, and most also complained about various facilities that do not support their comfort while studying. Keywords: Campus, Racing exhaust, Noise